Depression development in patients with OA, and its impact on treatment outcome - a literature review - Tołwiński, Ignacy; Dadas, Klaudia; Świercz, Aleksandra; Żurek, Urszula; Kędzierska, Zofia; Małachowska, Dominika; Ciecierski-Koźlarek, Hubert; Antkowiak, Klaudia; Popczyńska, Justyna; Woźniak, Kinga; et al. (Journal of Education, Health and Sport, 2023)
Introduction and aim of the study: Osteoarthritis (OA) and depression are leading causes of disease burden worldwide and important public health problems. A number of recent studies reported depression as a comorbidity of OA and its impact on reduced quality of life and worse treatment outcome of OA patients. The clinical management strategies of those patients still haven’t been developed, which is a challenge of future research on this topic. The aim of this review is to shed a light on important aspects of depression relationship with OA including its prevalence among OA patients and its influence on course and treatment of OA with a purpose of increasing awareness of this problem among physicians which may subsequently lead to a better overall medical care of patients with OA and depression. Methods and materials: This literature review is based on articles published in the PubMed database, GoogleScholar, ScienceDirect, and available medical textbooks. Conclusions: Recent literature reports a higher prevalence of depression among OA patients when compared to general population and its impact on osteoarthritis course, both on psychological and biomolecular level. Future research may lead to a better understanding of molecular background of depression and OA interrelation and to more complex and individualized management strategies which may result in a better outcome of treatment and improved life quality of osteoarthritis patients. Therefore, in order to optimize management of OA patients, physicians should pay more attention to depression and use multidisciplinary approach including assessment of mental health status to develop a more effective strategies of medical care in osteoarthritis.